Hydrogen sulfide adsorption on a defective graphene. Issue 6 (24th March 2012) - Borisova, Dobrina; Antonov, Vladislav; Proykova, Ana; Gidopoulos, Nikitas I.; Theophilou, Andreas K.
Abstract We have used density functional theory (DFT) to study adsorption of H2S molecules onto defective graphene as a function of vacancy concentration. The calculations are performed with the Quantum Espresso code, a plane‐wave realization of the DFT with norm‐conserving pseudopotentials. The Perdew et al. generalized gradient approximation to the density functional for exchange correlation energy of a many‐electron system is used. The computations show that a hydrogen sulfide molecule interacts stronger with the carbon atoms surrounding the vacancy than with the carbon atoms in a perfect arrangement. The most favorable energetically configuration is the one with the sulfur atom heading the center of the vacancy. Such a configuration facilitates covalent binding of the sulfur atom with three carbon atoms with unsaturated bonds. The density of states of perfect, defective graphene and defective graphene with chemisorbed sulfur demonstrate that the systems change their conductivity. The chemisorption is followed by a release of the hydrogen atoms, which form a H2 molecule. In the presence of more isolated vacancies per unit cell, more H2S molecules are chemisorbed. This process opens very interesting applications in the environmental and energy research. © 2012 Wiley Periodicals, Inc.